THE UTILIZATION OF PROXY SERVER ON THE INTERNET - Akbar Agung Riyadi (Jurnal Sistem Informasi, 2010)
Nowdays the information technology developments have taken place veryquickly. as well as with the internet. Even, the impact for using the Internet hasbecome an important requirement for the community. Internet itself, has a verywide range if we see from the coverage of the human and the computer thatconnected to each other. By using the Internet itself, we were guide to flown asif we do not have the borders between these countries. When the time anddistance was not a problem for the Internet in the terms of spreading theinformation, and if we think again about how the information can flow in theInternet easily, do you ever realize that the Internet can also be used to stealinformation on someone else? And after we knew this thing, what should we dothen? The most common method is to hide your IP address and using a proxyserver in one form or another. A proxy server is a computer that offers acomputer network service to allow clients to make indirect network connectionsto other network services. A client connects to the proxy server and thenrequests a connection, file, or other resource available on a different server. Theproxy provides the resource either by connecting to the specified server or byserving it from a cache. In some cases, the proxy may alter the client's request orthe server's response for various purposes. There are several implementations ofproxy servers that you can use to hide your IP address (in an attempt to remainanonymous on the internet ). In this scientific writing, me as the writers willexplain about the utilization of proxies server and various other things that canbe deemed relevant. I hope the readers can understand and obtain usefulinformation by reading these.